Mobile Health Applications: A Study on Awareness, Attitude and Practice among Medical Students in Sarawak - Pin Fen, Chua (14th National Conference of Clinical Research 2021, 2021)
Mobile Health Applications: A Study on Awareness, Attitude and Practice among Medical Students in Sarawak 1. JOHN JEMBAI Julian Valerie, Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak 2. WONG Yi Lin, Charlene, Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak 3. MUHAMMAD AMIR BAKHTIAR Nur Alia, Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak 4. MD LAZIM Siti Nursuraya, Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak 5. KUAN Pei Xuan, Digital Health Research and Innovation, Institute for Clinical Research 6. CHUA Pin Fen, Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak Introduction: In tandem with the Fourth Industrial Revolution (4IR), integrated mobile Health (mHealth) applications (apps) are important for the rapidly evolving digital healthcare. However, there are limited studies exploring on mHealth apps especially among medical students. Thus, we aim to assess the awareness, attitude and practice of mHealth apps among medical students. Methodology: We conducted a cross-sectional study among medical students in a government university in Sarawak from January to April 2021. Validated questionnaires on basic demographics, awareness, attitude and practice on mHealth apps (medical education, health and fitness and COVID-19 management) were administered to all consented students. Results: More than half of the respondents had high awareness for mHealth apps (medical education (61.8%), health & fitness (76.3%) and COVID-19 management (82.7%)). Positive attitude towards these apps were observed (97.2%, 98.4% and 73.5% respectively). However, less than half of the respondents have installed the medical education apps (n=89, 35.7%) and health and fitness apps (n=97, 39%). The practice of medical education apps was significantly associated with household income of the respondents (p<0.05) whereby the usage was seen most in T20 category. Respondents’ uncertainty to choose suitable apps was the most common barrier reported to the use of medical education apps (n=110, 68.8%) and health and fitness apps (n=112,73.7%) Discussion / Conclusion: The medical students had good awareness and attitude towards mHealth apps. However, the practice of using mHealth apps was relatively low. Thus. efforts to address the barriers and the promotion of use of mHealth apps are necessary.